STATE POLICY OF REGULATION OF FOOD IMPORT IN RUSSIA - V. Mintusov (Publishing House of the State University of Management, 2016)
The main directions of state regulation of import of food products in Russia are analyzed in the article. The emphasis is placed on mechanisms of the state support of agro-industrial complex. The characteristic of customs and tariff regulation of the food import in our country is given.